2023
DOI: 10.1186/s12879-022-07971-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-time analysis of hospital length of stay in a mixed SARS-CoV-2 Omicron and Delta epidemic in New South Wales, Australia

Abstract: Background The distribution of the duration that clinical cases of COVID-19 occupy hospital beds (the ‘length of stay’) is a key factor in determining how incident caseloads translate into health system burden. Robust estimation of length of stay in real-time requires the use of survival methods that can account for right-censoring induced by yet unobserved events in patient progression (e.g. discharge, death). In this study, we estimate in real-time the length of stay distributions of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…However, there were statistically significantly fewer hazards of death in Omicron than Delta in the study of Nyberg et al [14]. While we found faster ward-to-ICU transfer in omicron than delta, we did not evaluate the effects of other variables on this, but Tobin et al [18] showed that age was significantly affecting the time of ward-to-ICU transfer. Yet, we found that the hazard ratio for the age was 1.056 (95% CI 1.018-1.097, p =0.004), showing a 5.6% increase in death risk with a 1-year increase in age.…”
Section: Resultscontrasting
confidence: 59%
“…However, there were statistically significantly fewer hazards of death in Omicron than Delta in the study of Nyberg et al [14]. While we found faster ward-to-ICU transfer in omicron than delta, we did not evaluate the effects of other variables on this, but Tobin et al [18] showed that age was significantly affecting the time of ward-to-ICU transfer. Yet, we found that the hazard ratio for the age was 1.056 (95% CI 1.018-1.097, p =0.004), showing a 5.6% increase in death risk with a 1-year increase in age.…”
Section: Resultscontrasting
confidence: 59%
“…Moreover, the results of Ramin Sami et al's study reported an increase in the average length of stay in Isfahan hospitals in Iran during the Covid-19 pandemic(26). Of course, some previous studies have reported a decrease in the average length of stay during the Covid-19 pandemic (20,(27)(28)(29)(30)(31)(32) and others found no signi cant difference in the average length of stay during the Covid-19 pandemic (19). Longer length of stay at the onset of the pandemic can be attributed to the unknown nature of the disease and the lack of treatment guidelines, and as a result, the need for longer hospitalization (33).…”
Section: Discussionmentioning
confidence: 99%
“…The duration of hospitalisation in general wards and ICU follow a Gamma distribution, with means and variances sampled from estimates during the Australian Omicron outbreak. 18 Details of the clinical pathways model are given here. 10 .…”
Section: Clinical Pathwaysmentioning
confidence: 99%